A New Approach To Characterizing Particle Shape And Size - T. P. Meloy (Society for Mining, Metallurgy & Exploration, 1977)
Traditionally the mineral and mining engineers have characterized particles by sieving and-settling. Within the last decade, with the advent of the scanning microscope, entirely new experimental and theoretical approachesl-10/have been taken to minutely define the particle surface. This approach depends upon a hypothesis which takes advantage of the recent developments in automatic micro-scopes which can acquire large amounts of information in a short time and the new computational techniques which rapidly reduce the information to meaningful, practical data. Historically sieving and settling are the oldest sizing techniques known. Sieving by square screens, shown on Figure l-A is a common, current practice for sizing particles both in the laboratory and in production. A woven cloth is used which usually has square openings. The size particle that will pass through the opening dependent on a complex relationship of its morphology. As can be seen in Figure l-A, neither the width nor the height of the particle is determined by sieving. From square screens one and only one parameter characterizing the particle size is obtained, that parameter is the radius of the sphere that will just pass through the given sieve opening. A variation of square mesh screen is the slot screens, shown in Figure 1-B. Here another measure more closely associated with the height of the particle is obtained. Once again, one and only one parameter is associated with the particles' shape.